2021
DOI: 10.3390/ijms22168774
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Study of the Influence of Extracellular Vesicles Derived from Multipotent Stromal Cells on Osseointegration of Dental Implants

Abstract: Herein, the aim was to study the state of the bone tissue adjacent to dental implants after the use of extracellular vesicles derived from multipotent stromal cells (MSC EVs) of bone marrow origin in the experiment. In compliance with the rules of asepsis and antiseptics under general intravenous anesthesia with propofol, the screw dental implants were installed in the proximal condyles of the tibia of outbred rabbits without and with preliminary introduction of 19.2 μg MSC EVs into each bone tissue defect. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
2
Order By: Relevance
“…Outra forma de se aplicar a engenharia de tecidos a implantodontia é por meio do trabalho na superfície dos implantes. Para o pesquisador Americano Laird, et al, (2020) o revestimento da superfície de titânio liofilizando com solução nanoplex contendo 1% que foram submetidos ao uso de vesículas extracelulares derivadas de células estromais multipotentes de origem da medula óssea concluiu que essa terapêutica contribui para o aumento da densidade ósseo nos dispositivos, desenvolvendo uma osseointegração consistente nos implantes 10 dias após a operação (MAIBORODIN, et al, 2021).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outra forma de se aplicar a engenharia de tecidos a implantodontia é por meio do trabalho na superfície dos implantes. Para o pesquisador Americano Laird, et al, (2020) o revestimento da superfície de titânio liofilizando com solução nanoplex contendo 1% que foram submetidos ao uso de vesículas extracelulares derivadas de células estromais multipotentes de origem da medula óssea concluiu que essa terapêutica contribui para o aumento da densidade ósseo nos dispositivos, desenvolvendo uma osseointegração consistente nos implantes 10 dias após a operação (MAIBORODIN, et al, 2021).…”
Section: Discussionunclassified
“…As vesículas extracelulares são estruturas de até 50 nanômetros formadas por uma bicamada lipídica que apresenta em seu interior várias moléculas. Quando liberadas no exterior da célula de origem, essas alteraram o ambiente em que se encontram e podem se ligar a outras células quando dispostas a membrana de uma célula-alvo, ativando assim, os seus receptores de superfície para iniciar o processo de internalização, entregando seu conteúdo para desencadeando alterações citológicas (MAIBORODIN, et al, 2021).…”
Section: Discussionunclassified
“…Day 10 demonstrated that all animals with the use of MSC EVs had an almost complete fusion of the screw device with the bone tissue, while after the operation without the application of MSC EVs, the heterogeneous histologic pattern was observed, from almost complete osseointegration of the implant to the absolute absence of contact between the foreign body and the newly formed bone. Therefore, the use of MSC EVs during the introduction of dental implants into the proximal condyle of the tibia of rabbits contributes to an increase in the bone tissue density near the device after 3 days and to the achievement of consistently successful osseointegration of implants 10 days after the surgery [28].…”
Section: Research Findings and Their Discussionmentioning
confidence: 99%